1997
DOI: 10.1109/50.622889
|View full text |Cite
|
Sign up to set email alerts
|

Optical spectral amplitude CDMA communication

Abstract: We report the first demonstration of bipolar coding techniques in the optical spectral domain for incoherent optical code division multiple access (CDMA) communication. Based on the modulation and detection principles that we have developed, the power spectrum of an erbium-doped superfluorescent fiber source was encoded using bipolar codes and decoded using an optical bipolar correlator. A CDMA testbed consisting of two encoders and one decoder was implemented with bulk optics and free-space transmission. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…We notice that most of the reported experiments [26][27][28][29][30] employ spread spectrum technology and DSF, while the reports of high speed unipolar OCDMA experiments [1,31] are relatively less. Ultrashort optical pulse and dispersion effect may be the obstacle to fulfill the unipolar OCDMA system.…”
Section: Optical Hard Limitermentioning
confidence: 97%
“…We notice that most of the reported experiments [26][27][28][29][30] employ spread spectrum technology and DSF, while the reports of high speed unipolar OCDMA experiments [1,31] are relatively less. Ultrashort optical pulse and dispersion effect may be the obstacle to fulfill the unipolar OCDMA system.…”
Section: Optical Hard Limitermentioning
confidence: 97%
“…We used LC-SLM to encode the power spectrum of a source into bipolar Walsh codes for data modulation. The coding principle is the same as that described by Young et al 27) in which a bipolar code was represented as two unipolar codes, as shown in Fig. 2.…”
Section: Operational Principlesmentioning
confidence: 99%
“…Here we limit our analysis to a synchronous system. For on-off-keyed modulation, the E field received by the ith decoder can be written as [30]…”
Section: Spects O-cdma Architectures Protocols and Performance Simumentioning
confidence: 99%